Improvement of Upper Extremity Deficit after Constraint-Induced Movement Therapy Combined with and without Preconditioning Stimulation Using Dual-hemisphere Transcranial Direct Current Stimulation and Peripheral Neuromuscular Stimulation in Chronic Stroke Patients: A Pilot Randomized Controlled Trial - Takebayashi, Takashi; Takahashi, Kayoko; Moriwaki, Misa; Sakamoto, Tomosaburo; Domen, Kazuhisa (Frontiers in Neurology, 2017)
In this study, we investigated the effects of dual-hemisphere transcranial direct current stimulation (dual-tDCS) of both the affected (anodal tDCS) and non-affected (cathodal tDCS) primary motor cortex, combined with peripheral neuromuscular electrical stimulation (PNMES), on the effectiveness of constraint-induced movement therapy (CIMT) as a neurorehabilitation intervention in chronic stroke. We conducted a randomized controlled trial of feasibility, with a single blind assessor, with patients recruited from three outpatient clinics. Twenty chronic stroke patients were randomly allocated to either the control group, receiving conventional CIMT, or the intervention group receiving dual-tDCS combined with PNMES before CIMT. Patients in the treatment group first underwent a 20-min period of dual-tDCS, followed immediately by PNMES, and subsequent CIMT for 2 hours. Patients in the control group only received CIMT (with no pre-treatment stimulation). All patients underwent two CIMT sessions, one in the morning and one in the afternoon, each lasting 2 hours, for a total of 4 hours of CIMT per day. Upper-extremity function was assessed using the Fugl-Meyer Assessment (primary outcome), as well as the amount of use (AOU) and quality of movement scores (QOM), obtained via the Motor Activity Log (secondary outcome). Nineteen patients completed the study, with one patient withdrawing after allocation. Compared to the control group, the treatment improvement in upper-extremity function and AOU was significantly greater in the treatment than control group (change in upper-extremity score, 9.20±4.64 versus 4.56±2.60, respectively, P < 0.01, η2 = 0.43; change in AOU score, 1.10±0.65 versus 0.62±0.85, respectively, P = 0.02, η2 = 0.52). There was no significant effect of the intervention on the QOM between the intervention and control groups (change in QOM score, 1.00±0.62 versus 0.71±0.72, respectively, P = 0.07, η2 = 0.43; treatment versus control). Our findings suggest a novel pre-treatment stimulation strategy besed on dual-tDCS and PNMES may enhance the therapeutic benefit of CIMT.